Exploring Beauty Standards and Physical Markers of Beauty: What Shapes Perceptions of Beauty amongst Coloured Students at a Historically White University in the Western Cape? - Elias, Donne Amber (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.